The need for interdisciplinary research in marine sciences – A MERry outlook - von Hellfeld, Rebecca; Sujiwo, Aryo Sahid; Seeram, Salomi; Olatunji, Paul Oluwatimileyin; Parga Martinez, Karla; Govindankutty Menon, Anjaly; Beckmann, Clara; Marigómez, Ionan; Soto, Manu (Frontiers in Marine Science, 2024)
The global oceans are facing a plethora of pressures, leading to cross-national impacts on marine ecosystems, wildlife, and resource users. Interdisciplinarity is integrating knowledge and methods from different disciplines to generate a comprehensive output. Due to the trans-boundary nature of marine habitats and stressors, interdisciplinary research forms the basis to addressing pressing matters in ocean health and conservation. To this end, the Marine Environment and Resources (MER) master programme was developed at the beginning of the century, enabling students to develop a well-rounded understanding of ocean science. The programme has since become a recognised Erasmus Mundus degree and has had almost 400 graduates. In September 2022, the first MER community summit was held, being a landmark for the building of a long-lasting global community to discuss and deal with priority challenges of the UN Decade of Oceans Science. This summit has highlighted that to understand the state of the oceans and improve conservation efforts, international collaboration is required (including those out with the academic realm). The following article aims to highlight the successes of the programme in aiding the development and training of interdisciplinary researchers from a plethora of backgrounds, uniquely suitable for addressing current problems.